2018
DOI: 10.2134/jeq2018.07.0277
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Water Quality: Monitoring and Modeling

Abstract: Microbial water quality lies in the nexus of human, animal, and environmental health. Multidisciplinary efforts are under way to understand how microbial water quality can be monitored, predicted, and managed. This special collection of papers in the Journal of Environmental Quality was inspired by the idea of creating a special section containing the panoramic view of advances and challenges in the arena of microbial water quality research. It addresses various facets of health‐related microorganism release, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 60 publications
1
24
0
1
Order By: Relevance
“…In developing countries, untreated surface water is often used for drinking, cooking, bathing and washing, thus exposing the population to a high health risk (Boithias et al, 2016). Catchment microbial response depends on complex interactions between spatial patterns of land use, soil types, antecedent conditions of soil, and rainfall characteristics (Kim et al, 2018;McKergow and Davies-Colley, 2010;Pachepsky et al, 2018;Strauch et al, 2014). In the tropics, the presence in stream water of Fecal Indicator Bacteria (FIB), such as Escherichia coli (E. coli), is known to be partly driven by surface runoff (Causse et al, 2015;Ribolzi et al, 2016a) and groundwater flow (Chuah and Ziegler, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, untreated surface water is often used for drinking, cooking, bathing and washing, thus exposing the population to a high health risk (Boithias et al, 2016). Catchment microbial response depends on complex interactions between spatial patterns of land use, soil types, antecedent conditions of soil, and rainfall characteristics (Kim et al, 2018;McKergow and Davies-Colley, 2010;Pachepsky et al, 2018;Strauch et al, 2014). In the tropics, the presence in stream water of Fecal Indicator Bacteria (FIB), such as Escherichia coli (E. coli), is known to be partly driven by surface runoff (Causse et al, 2015;Ribolzi et al, 2016a) and groundwater flow (Chuah and Ziegler, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying observations with uncertain predictions is an approach to determine the set of data requiring optimization and thus find a way to optimize the collection and to efficiently complete our training set, allowing for a better prediction in the future by re-running the model with the newly collected measurements. Indeed, recent studies have shown that increasing the quality and quantity of the dataset by adding complementary measures allows to effectively increase the training set and to improve prediction accuracy [20,43].…”
Section: Limits Of Ml-based E Coli Estimationmentioning
confidence: 99%
“…9 Drinking water if drawn from such sources, generally contains various pathogenic microorganisms and it turns out difficult to treat and deliver clean drinking water as the pathogens vary depending on the source of the contamination. 10 The Jia-Bharali river basin is one of the most evolved regions in the north Brahmaputra plain of India. 11 The area has broad tea-estates and paddy fields.…”
Section: Introductionmentioning
confidence: 99%